The Role of Islamic Financial Education in Encouraging Customer Investment Behavior in Islamic Banking in Yogyakarta, Indonesia - Syarif As'ad; Muhammad Safar Nashir; Sahraman D. Hadji Latif (Universitas Muhammadiyah Yogyakarta, 2024)
This paper investigated the moderating effect of Islamic financial education on the relationship between information management and customer perception regarding the increase in investments at Bank Syariah Indonesia, using conventional sampling techniques for data collection from respondents in Yogyakarta. A closed questionnaire comprising 35 items was prepared and tested before the commencement of the study. Path analysis in PLS was utilized as the primary tool to analyze the 141 respondents who completed the survey. The research revealed that the moderating factors have both direct and indirect moderation effects on customer financial investments in Bank Syariah Indonesia, indicating that information management and customer perception are crucial factors in enhancing customer investments. Accordingly, the study was limited to the collection of quantitative data using a semi-structured questionnaire from Yogyakarta, and there is an opportunity to test these findings in other major cities, including those in other developing countries. From a practical perspective, this study elucidates that Islamic financial education plays a significant role in increasing the value of customer investments in Bank Syariah Indonesia, thereby potentially expanding the market share of Islamic banks in Indonesia.